Interactive motions of two offshore structures in close proximity - Thong, Jin Hong, 1987-, author; Adi Maimun Abdul Malik, supervisor; Fakulti Kejuruteraan Mekanikal (2011)
Project Paper (Sarjana Muda Sains (Rekabentuk Industri)) - Universiti Teknologi Malaysia, 2011